Effect of Price and Product Quality on Purchasing Decisions Onions in Bima Regency - Sri Ernawati zunaidin; Ismunandar Ismunandar; Ni Wayan Ari Sudiartini (Enrichment : Journal of Management, 2022)
Onions are one of the leading vegetable commodities in Indonesia which have been intensively cultivated by farmers for a long time. This vegetable commodity belongs to the group of non-substituted spices that function as food seasonings as well as ingredients for traditional medicines. This study aims to determine the effect of price and product quality on the decision to purchase onions in Bima Regency. This study uses a quantitative approach with a survey method. While this type of research is categorized as causal research with the number of samples in this study amounting to 100 people with the research instrument using a questionnaire with a Likert scale. Data collection techniques using questionnaires, observations and literature studies. Data analysis used multiple linear regression and hypothesis testing using t test and f test. The results of hypothesis testing state that partially the price has an effect on purchasing decisions where the tcount value is 4.477 with a t table value of 1.66071 (4,477˃1.66071), product quality has no effect on purchasing decisions where the t count value is 1,428 with a t table value of 1, 66071 (1,428<1,66071), and simultaneously it can be stated that the price and product quality affect the decision to purchase onions in Bima Regency where the fcount value is 40,097 with the ftable value 3,09 (40.097 >3.09)